2020
DOI: 10.32615/ps.2019.165
|View full text |Cite
|
Sign up to set email alerts
|

Special issue in honour of Prof. Reto J. Strasser - Thylakoid membrane reorganization, induced by growth light intensity, affects the plants susceptibility to drought stress

Abstract: One of the major questions in photosynthesis research is related to the role of the ultrastructure of thylakoid membranes in higher plants for their functional performance at optimal and stress environmental conditions. In this work, we compared the drought stress response of pea plants grown at moderate and low light conditions, based on our recent findings that they differ in the extent of grana stacking and in the thermal stability of the major light-harvesting complex of PSII that plays important regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…In contrast, Lawlor and Tezara (2009) argued that solar energy absorption, energy transfer from the antenna to the reaction centre, charge separation or electron transfer from the reaction centre to pheophytin and Q A occur in the hydrophobic lipid‐protein matrix of thylakoidal membranes, which are insensitive to lower RWC range, that is, 60–50%. While assessing the impact of tissue RWC on thylakoidal membrane organisation and PSII damage in drought‐stressed plants of pea, Petrova et al (2020) found that, at less than 60% RWC, drought stress causes the disassembly of the LHCII‐PSII super complexes and the disintegration of core proteins by decreasing membrane hydration or membrane fluidity. Long ago, Navari‐Izzo et al (2000) demonstrated that an increase in unsaturated fatty acids upon drought‐induced reduction in membrane fluidity was the principal protection of PSII in the resurrection plant Boea hygroscopica .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Lawlor and Tezara (2009) argued that solar energy absorption, energy transfer from the antenna to the reaction centre, charge separation or electron transfer from the reaction centre to pheophytin and Q A occur in the hydrophobic lipid‐protein matrix of thylakoidal membranes, which are insensitive to lower RWC range, that is, 60–50%. While assessing the impact of tissue RWC on thylakoidal membrane organisation and PSII damage in drought‐stressed plants of pea, Petrova et al (2020) found that, at less than 60% RWC, drought stress causes the disassembly of the LHCII‐PSII super complexes and the disintegration of core proteins by decreasing membrane hydration or membrane fluidity. Long ago, Navari‐Izzo et al (2000) demonstrated that an increase in unsaturated fatty acids upon drought‐induced reduction in membrane fluidity was the principal protection of PSII in the resurrection plant Boea hygroscopica .…”
Section: Discussionmentioning
confidence: 99%
“…Light availability is a determinant environmental factor in the capacity of plants in silvicultural activities since the plants can be inserted in open areas, clearings, understories, or dense forests in different vegetation and/or agroforestry systems. Thus, high or low light intensity can be a stressful condition affecting the production of photoassimilates since it correlates with the thylakoid structure (Petrova et al, 2020), mesophilic conductance, and carboxylation efficiency of RuBisCO (Mendes et al, 2017), and overall photosynthesis. On the other hand, some species can acclimatize to these conditions, adjusting their metabolism through receptors that control the expression of cell division genes and the formation of meristematic tissues (Anpo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This advantage is attributed to the different morphological, anatomical, and biochemical mechanisms used during carbon fixation in C3 and C4 species (Pearcy and Ehleringer 1984). C4 species can increase energy consumption efficiency through energy conservation and thereby maintain a higher photosynthetic performance and water-use efficiency than C3 species under water-stress conditions (Majeran et al 2010, Petrova et al 2020. While water stress can lead to an excess of energy absorbed by the leaves associated with altered CO2 assimilation, C4 species tend to be better adapted to high light and temperature intensities than C3 species (Guidi et al 2019).…”
Section: Introductionmentioning
confidence: 99%